100 questions and answers to help you land your dream iOS job or to hire the right candidate! - Mañas, Enrique López (Apress, 2019)
Are you an iOS developer, looking forward to your next career move? Or are you interviewing for positions at your company or start-up? Either way, this book provides the right questions and answers to help you in the review process. If you are an interviewer, this book can guide you on which questions are the most useful to ask to find the perfect candidate. Generic interview questions found online are repetitive and often unrelated to the day-to-day tasks of an iOS developer. If you are aiming at hiring a professional programmer you should consider more advanced questions about architecture, patterns, or frameworks such as those included in this book. All questions are answered clearly and comprehensively and each one is categorized and reviewed from some of the top iOS engineers worldwide. Some of the questions provide quick follow-ups, which might make the difference between a good enough answer and a stellar one. Questions are divided in three different levels, so whether you are a beginner or an advanced iOS developer, this book will help you to land your dream iOS development Job!
Includes index. - Online resource; title from cover (viewed February 11, 2019)
Keywords: iOS (Electronic resource); Computer software developers -- Vocational guidance; Développeurs de logiciels; Orientation professionnelle